Informality in Urban Areas, a Case of Land Use Transformation in Mlalakuwa Settlement, Dar es Salaam - Najum Juma; Nelly Babere (African Journal on Land Policy and Geospatial Sciences, 2020)
Land use development and transformation in informal settlements have been taking place because informal settlements have been alternative way of providing affordable housing to low income people. Many governments use strict regulations to deny informal settlements from infrastructure services but in Tanzania informal settlements are provided with such services. This paper presents the findings on how land use transformation is taking place and publicly used spaces disappear overtime in the informal settlements, the context behind and their outcomes. Based on field observation and mapping process, the study analyzed the process and different types of land use transformation which were horizontal, vertical and horizontal-vertical. Also through interviews, observation and documentary review, the study identified context and outcomes of the transformation process. Factors contributed to land use transformation in the study area were socio-economic and spatial factors and outcomes were socio-economic, environmental and spatial outcomes.